Treating opioid use disorders in the criminal justice system with pharmacotherapy - Susan Schenk (Forensic Science International: Mind and Law, 2020)
Background: People who suffer from opioid use disorders (illicit and prescription opioids) are disproportionately involved in criminal activities and a high percentage of those incarcerated suffer from these disorders. Despite the established efficacy of pharmacotherapy for opioid use disorders this intervention is infrequently offered to criminal justice populations. This review sets out to understand the nature of the relationship between opioid use disorders and criminal offending and the efficacy of pharmacotherapy in reducing both relapse and criminal recidivism, with a view to informing policy and practice. Methods: A narrative review of the published literature in the area of opioid use, criminal offending, and pharmacotherapy efficacy, was undertaken. Results: The evidence shows that (1) there is a high prevalence of opioid misuse in the criminal offending population; (2) criminal recidivism amongst those with an opioid use disorder is high (3) pharmacotherapy proves effective for opioid use disorders during and after incarceration, and (4) pharmacotherapy for offending populations decreases both relapse to drug-taking and criminal recidivism. Conclusion: The findings show that responding to opioid use disorders in the criminal justice system with pharmacotherapy is warranted.